Molecular Cloning of the m-Golsyn Gene and its Expression in the Mouse Brain - Funakoshi, Eishi (Gene Expr, 2018)
The mouse ortholog of the human GOLSYN gene, termed the m-Golsyn gene, was isolated and mapped to the region on mouse chromosome 15B3.2 syntenic with human chromosome 8q23. Three mRNA species (type 1a, 1b, and type 2) were produced by use of alternative transcription initiation points and alternative splicing events. The type 1 mRNAs were expressed only in the brain, whereas the type 2 was detected in various tissues. m-Golsyn protein was expressed in various tissues including the brain. Immunohistochemical study of m-Golsyn protein showed its prominent expression in the neuronal cells in various regions of the brain and strong expression in the choroid plexus ependymal cells lining the ventricles. m-Golsyn protein was found to be homologous to syntaphilin, a regulator of synaptic vesicle exocytosis. These results indicate that the m-Golsyn protein may play an important role in intracellular protein transport in neuronal cells of the brain.